(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Because lung cancer (L.C) still has a high incidence and mortality rate, it is essential to create an effective tool for early diagnosis. The serum can represent both pathologic and physiological impacts on a person, hence the FTIRATR approach was used to assess serum samples from both normal and (L.C) patients. The lipid, protein, and nucleic acid molecule concentrations on the serum of lung cancer patients were identified by the comparison of band spectral region. Cancer rates were increased compared to those who were in good health. Through this study, the spectra of samples of patients with an average age 58.49091±14.006444 and for healthy patients with an average age 58.56667±13.748187 and using independent test to found that the ratio R1(2959/1544) being effective to identifying the serum of (L.C) patients from the serum of normal. Additionally, the findings demonstrated that the (helix/sheet) ratios in (L.C) patients' serum were higher than those in normal serum. Additionally, it was shown that there is a statistically significant correlation between the patient and healthy group ratios that were looked at. Additionally, A2 and A9, as well as A4 and A6, had a high Pearson correlation that was statistically significant whether it was positive or negative. Accordingly, it can be argued that this study is the first of its sort for the Karbala Governorate, and its information can be regarded as crucial for subsequent research.